Contact Forces in a Screw Feeding Process - Yunfei Shi; Xiliang Zhang; Shoujuan Cui; Kui Ma (Advances in Materials Science and Engineering)
The contact force between particles is analysed in this paper. Firstly, theoretical analysis is carried out based on the Hertz–Mindlin (no slip) model. Secondly, the normal force and tangential force are, respectively, simulated in single/double-flight screw feeders with the discharging device at three rotating speeds (60 rpm, 90 rpm, and 120 rpm) using different diameter particles (3 mm,  5 mm, and 7 mm) by the extended distinct element method (EDEM) software. Finally, the simulation results show that the particle diameter has the biggest impact on average contact force in the feeding process. This research provides theoretical basis for the study of the rule of bulk material movement in the screw feeder and the development of the high-precision feeding machine.